Kardiochirurgia dorosłych Radial artery in surgical treatment of coronary artery disease - Żelazny, Piotr; Religa, Grzegorz; Kołsut, Piotr; Buzun, Leszek; Szapiel, Grzegorz; Pawlak, Sebastian; Kaszczyński, Tomasz; Socik, Jolanta; Jasińska, Małgorzata (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Background: The radial artery’s role in coronary revascularization was undervalued for many years. Recently it acquired its particular place in this field of surgery. Aim: Evaluation of radial artery appliance in coronary revascularization. Material and methods: From February 1997 until December 2005 the radial artery was used in 628 patients who underwent coronary artery revascularization. It was used in various types of revascularization procedures and in different configurations. In 125 patients (25%) RA was used in combined venous-arterial grafting, in 306 patients (48.57%) in total arterial revascularization carried out by the traditional method, and in 166 patients (26.43%) it was applied as an arterial conduit in procedures using “aorta no-touch technique” – T and Y grafts or in “arterial sling operations”. The same standardized regimen of radial artery harvesting was used as well as peri- and postoperative calcium channel blocker administration. Results: The in-hospital mortality rate was 3.34 % (21patients). Early postoperative spasm of RA confirmed by angiography appeared in 3 patients (0.48%). There were no symptoms of limb ischaemia after RA harvesting in any case. Conclusions: Despite the radial artery’s propensity to spasm it has many advantages and has become a very useful vessel for artery grafting.